Future Anxiety and Immune Status in Nursing Students During the Coronavirus Disease-2019 Pandemic - Agus Purnama; Isti Anindya (Jurnal Keperawatan Indonesia, 2022)
Coronavirus Disease-2019 (COVID-19) is a frightening global disease, especially because of its high contagiousness. This study aimed to identify the future anxiety regarding immunity status in nursing students who work in hospitals, especially those caring for patients with COVID-19. This study design was cross-sectional with standard translated instruments of the Future Anxiety Scale and Immune Status Questionnaire administered using a Google Form to 102 respondents. Results revealed that among the respondents, 87 experienced severe psychological anxiety (85.3%), 46 experienced moderate social anxiety (45.1%), 42 experienced moderate economic anxiety (41.2%), 38 experienced mild media anxiety (37.3%), 53 experienced mild religious anxiety (52%), 45 experienced moderate general anxiety (44.1%), and 61 had mostly good immunity status (59.8%). The relationship between psychological, social, economic, media, and general anxiety with immunity status was (p = 0.835), (p = 0.052), (p = 0.514), (p = 0.414), (p = 0.160), and (p = 0.123), respectively. In conclusion, a dominant future anxiety rate was found in the respondents but showed no relationship with immunity status. Future studies must include heterogeneous respondents and moderate variables to further improve the accuracy of the findings. The present results serve as justification for a program to address anxiety in nursing students during clinical practice in pandemic times.   Abstrak Kecemasan Masa Depan dan Status Imun pada Mahasiswa Keperawatan Selama Pandemi COVID-19. CoronavirusDisease-2019 (COVID-19) menjadi salah satu penyakit yang menakutkan di masyarakat global, terlebih karena sifat penularannya yang tinggi. Tujuan penelitian ini adalah untuk mengidentifikasi kecemasan masa depan mahasiswa keperawatan yang bekerja di rumah sakit, khususnya yang merawat pasien COVID-19, terhadap status imunitas mahasiswa itu sendiri. Penelitian ini adalah cross-sectional, dengan menggunakan terjemahan dari Future Anxiety Scale (FAS) dan Immune Status Questionnaire (ISQ) dengan yang difasilitasi aplikasi Google Formulir kepada 102 mahasiswa keperawatan. Hasil penelitian menunjukkan sebanyak 87 responden mengalami kecemasan psikologis berat (85,3%), kecemasan sosial sedang 46 (45,1%), kecemasan ekonomi sedang 42 (41,2%), kecemasan media ringan 38 (37,3%), kecemasan religi ringan 53 (52%), kecemasan umum sedang 45 (44,1%), status imunitas sebagian besar baik 61 (59,8%). Hubungan antara kecemasan psikologis, sosial, ekonomi, media, dan kecemasan umum dengan status imunitas yaitu (p = 0,835), (p = 0,052), (p = 0,514), (p = 0,414), (p = 0,160), dan (p = 0,123). Kesimpulan pada penelitian ini adalah terdapat angka kecemasan masa depan yang dominan pada responden tetapi tidak ditemukan hubungannya dengan status imunitas. Pada studi selanjutnya, perlu dilakukan pendekatan penelitian dengan melibatkan responden yang lebih heterogen dengan mempertimbangkan memasukkan variabel moderat untuk lebih meningkatkan akurasi penelitian yang dilakukan. Hasil penelitian ini menjadi suatu justifikasi tentang perlunya sebuah program untuk mengatasi kecemasan pada mahasiswa keperawatan selama praktik klinik di masa pandemi. Kata Kunci: COVID-19, imunitas, kecemasan masa depan, perawat